Sozdadim lesnyye polosy! - Teriovskaya (ОГИЗ - ИЗОГИЗ (Izogiz), 1935)
Landscape of wheat fields separated by hedges of trees, some as forests, some as saplings, with workers planting them. Edges of poster depicting diagrams of leaves and flowers, and other information Original title: Создадим лесные полосы!. Suggested translation: Create forest strips! PO-0014